Dakwah Rahmatan lil al-Alamin as Solutive Da'wah: A Study of the Study of Tafsir Science with the Approach of Sharah Hadith - M. Irfan Farraz Haecal Kusnadi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The purpose of writing this article is to discuss how true Islamic da'wah is in accordance with the context of